2020
DOI: 10.1177/0954406220906445
|View full text |Cite
|
Sign up to set email alerts
|

Electric discharge machining using rapid manufactured complex shape copper electrode: Parametric analysis and process optimization for material removal rate, electrode wear rate and cavity dimensions

Abstract: The present investigation addresses the machining outcome of electric discharge machining using a rapid manufactured complex shape copper electrode. Developed rapid manufacturing technique using an amalgamation of polymer 3D printing and pressureless sintering of loose powder as rapid tooling has been used to fabricate copper electrode from the computer-aided design model of the desired shape. The fabricated electrode was used for the electric discharge machining of the D-2 steel workpiece. Central composite d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In the last few years, several researchers have thus explored beamless AM methods for the fabrication of metal parts. Some methods combine polymer 3D printing and other conventional manufacturing processes such as casting, sintering, electroforming, and spraying [8][9][10][11][12][13]. This opens the way to the fabrication of metal parts at low cost due to less capital investment, less material consumption, and low-skilled worker requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, several researchers have thus explored beamless AM methods for the fabrication of metal parts. Some methods combine polymer 3D printing and other conventional manufacturing processes such as casting, sintering, electroforming, and spraying [8][9][10][11][12][13]. This opens the way to the fabrication of metal parts at low cost due to less capital investment, less material consumption, and low-skilled worker requirements.…”
Section: Introductionmentioning
confidence: 99%
“…47 The EDM parameters used in the present study were optimized to achieve maximum MRR and minimum EWR and dimensional deviation of the machined cavity as compared to the CAD model. 39 Therefore, the complex shape cavity dimensions were found to be near about the CAD model dimensions machined with the RME (ref. Table 2).…”
Section: Resultsmentioning
confidence: 84%
“…The EDM was performed at the optimized machining parameter (pulse duration = 391 µs, duty cycle = 75% and peak current = 6 A). The parameters were optimized using design of experiments approach and genetic multi-objective optimization algorithm for the maximization of MRR and minimization of EWR and dimension deviation of the EDM cavity from CAD model by rapid manufactured solid copper electrode in the previous study by Singh et al 39…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its unique properties, the idea of obtaining composite materials consisting of a metal matrix and graphene has been developed for the past decades. It was found that the introduction of graphene into a metal matrix results in an increase its mechanical resistance and strength [ 6 , 7 , 8 , 9 , 10 ]. Graphite inclusions improve the impact strength of layered carbon/Ni and carbon/Cu composites [ 11 ].…”
Section: Introductionmentioning
confidence: 99%